Analisis Organoleptik Hedonik Sambal Ikan Layang Asin Kering dengan Penambahan Rumput Laut - Nupu, Abdul Kadir; Mile, Lukman; Yusuf, Nikmawatisusanti (The NIKe Journal, 2023)
This study aims to determine the effect of the addition of seaweed (Kappaphycus alvarezii) on the hedonic organoleptic characteristics of the dried salted catfish (Decapterus sp.) chili product. The treatments in this study were seaweed concentrations of 5%, 10% and 15%. The hedonic organoleptic data analysis used was Kruskall-wallis with test parameters namely taste, appearance, texture, aroma and color. Further test using the Duncan test. The results showed that the addition of seaweed had no significant effect on the hedonic value of taste, appearance, texture, aroma and color. The hedonic characteristics of chili sauce with the addition of different seaweeds have a taste value of 6.08–7.00 with the criteria of slightly liking to liking; appearance 7.00-7.28 with Like criteria; texture 6.88–7.24 with liking criteria; aroma 6.80–7.32 with liking criteria; and color 6.92–7.52 with liking criteria.